OPERANT BEHAVIOUR OF LITHOGENIC FEED FOR EXPERIMENTAL PURPOSES - HANICHEV, B.М. HANICHEV; GAHOKAST, V .S. GAHOKAST (International Journal of Multidisciplinary Research and Studies, 2021)
In the present work, the influence of natural zeolites on the parameters of defensive behavior was analyzed in experiments with white laboratory rats and a modular device. The obtained data suggested that among the experimental individuals under conditions of tool stress, 76% preferred the food that contained a mineral additive within the kind of a crushed zeolite, while the symptoms of behavioral activity were optimized within the given category of animals.